The boyds of Black river - Edmonds, Walter Dumaux 1903-1998 (Dodd, Mead, 1953)
A story of a family of horse breeding farmers in the Black River area of Upstate New York in the early 1900's.
Keywords: Geschichte; New York (State) -- History -- Fiction